Analysis of Initial Ability and Visual Thinking Ability of Grade X High School Students in Trigonometry Competence - Nur Khotibah; Ahmad Yani T; Agus Winarji; Mohammad Rif'at; Metia Novianti (STKIP Singkawang, 2026)
This study investigated students’ prior knowledge, visual thinking ability, and the relationship between both aspects in learning trigonometry among tenth-grade students at SMAN 10 Pontianak. The study was motivated by the importance of prerequisite knowledge in supporting conceptual understanding and by the role of visual thinking in interpreting abstract trigonometric concepts. A qualitative approach with a case study design was employed. Six students from class X-A were selected purposively to represent high, moderate, and low levels of visual thinking ability. Data were collected through prior knowledge tests, visual thinking tests, and semi-structured interviews. Visual thinking was examined through four indicators: looking, seeing, imagining, and showing and telling. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that students’ prior knowledge and visual thinking ability were categorized into high, moderate, and low levels. Students with strong prior knowledge were generally able to construct accurate visual representations and apply concepts systematically. In contrast, students with limited prior knowledge experienced difficulties, particularly in the imagining stage, because they struggled to connect prerequisite concepts with visual problem-solving processes. The study indicates that prior knowledge contributes to the quality of students’ visual representations and influences the consistency of concept application in solving trigonometry problems. Therefore, strengthening prerequisite concepts is necessary to support the development of visual thinking skills in mathematics learning.Analisis Kemampuan Awal dan Kemampuan Berpikir Visual Peserta Didik Kelas X SMA pada Kompetensi TrigonometriABSTRAKPenelitian ini bertujuan untuk menganalisis kemampuan awal, kemampuan berpikir visual, serta keterkaitan antara kemampuan awal dan kemampuan berpikir visual peserta didik kelas X SMAN 10 Pontianak pada materi trigonometri. Penelitian ini dilatarbelakangi oleh pentingnya kemampuan awal sebagai dasar pemahaman konsep serta peran kemampuan berpikir visual dalam membantu peserta didik merepresentasikan konsep trigonometri yang bersifat abstrak. Penelitian menggunakan pendekatan kualitatif dengan jenis studi kasus. Subjek penelitian terdiri dari enam peserta didik kelas X-A yang dipilih menggunakan teknik purposive sampling berdasarkan kategori kemampuan berpikir visual tinggi, sedang, dan rendah. Data diperoleh melalui tes kemampuan awal, tes kemampuan berpikir visual, dan wawancara semi terstruktur. Kemampuan berpikir visual dianalisis berdasarkan indikator looking, seeing, imagining, serta showing and telling. Data dianalisis melalui tahap reduksi data, penyajian data, dan penarikan kesimpulan. Temuan penelitian memperlihatkan adanya perbedaan tingkat penguasaan kemampuan awal dan kemampuan berpikir visual peserta didik yang dapat dikelompokkan ke dalam kategori tinggi, sedang, dan rendah. Peserta didik dengan kemampuan awal tinggi cenderung mampu membangun representasi visual secara tepat dan sistematis. Sebaliknya, peserta didik dengan kemampuan awal rendah mengalami kesulitan pada indikator imagining karena belum mampu menghubungkan konsep prasyarat dengan visualisasi penyelesaian masalah. Temuan penelitian menunjukkan bahwa kemampuan awal memengaruhi kualitas representasi visual dan konsistensi penggunaan konsep dalam penyelesaian soal trigonometri. Oleh karena itu, penguatan konsep prasyarat perlu dilakukan untuk mendukung kemampuan berpikir visual peserta didik dalam pembelajaran trigonometri.Kata Kunci :Kemampuan Awal; Kemampuan Berpikir Visual; Trigonometri